Enhanced aerodynamic performance of NACA4412 airfoil through integrated plasma actuator and Gurney flap flow control - K.V. Karthikeyan; R. Harish (Results in Engineering)
This study explores advanced flow control techniques for enhancing the aerodynamic efficacy of the NACA4412 airfoil. By employing a combination of passive and active flow control methods, this research aims to improve lift and reduce drag, particularly at higher angles of attack (AOA). The investigation numerically models the three-dimensional incompressible and unsteady flow over the airfoil using Large Eddy Simulation (LES) with the Smagorinsky model for subgrid scale effects. The simulations are conducted at a Reynolds number of 3.1×106, with AOA ranging from 0∘ to 20∘. The study employs a gurney flap with a fixed width of 2 mm and variable heights from 1% to 3% of the chord length, in conjunction with a dielectric barrier discharge (DBD) plasma actuator positioned at a distance of 2% from the leading edge of the chord. Gurney flap significantly enhances lift at lower AOA, increasing it by 35% to 83%. When combined with the plasma actuator, the lift at higher AOA improves dramatically, ranging from 47% to 140%. While the gurney flap alone slightly increases drag at lower AOA, the combination of plasma actuator with gurney flap reduces drag at higher AOA by up to 8%, demonstrating greater efficiency. The study also visualizes vortex formation around the gurney flap, noting that increased vortex activity reduces flow separation. Furthermore, increasing the plasma actuator voltage from 5.67 kV to 6 kV significantly reduces flow separation, enhancing overall flow control.